Environmental policy analysis and practice - Greenberg, Michael R. (Rutgers University Press, 2007)
Pressing environmental challenges are frequently surrounded with stakeholders on all sides of the issues. Opinions expressed by government agencies, the private sector, special interests, nonprofit communities, and the media, among others can quickly cloud the dialogue, leaving one to wonder how policy decisions actually come about. In Environmental Policy Analysis and Practice, Michael R. Greenberg cuts through the complicated layers of bureaucracy, science, and the public interest to show how all policy considerations can be broken down according to six specif.